Good Financial Governance in Village and Public Sector Area: What We Need? - Narastri, Maulidah (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This paper aims to provide an overview of the implementation of good financial governance within the context of villages and the public sector. The methodology employed in this study is qualitative in nature, utilizing a literature review approach. The findings indicate that there are several essential components required to achieve good financial governance, namely: Transparent Budget Planning, Effective Budget Execution, Accountability and Transparency, Internal and External Oversight, Capacity Building of Financial Managers, and Community Participation. Conversely, the absence of good financial governance may lead to several negative consequences, including: Misuse of Funds and Corruption, Inequitable Resource Allocation, Loss of Public Trust, Resource Wastage, Limited Infrastructure and Public Service Development, Ineffective Policy Implementation, Constraints on Sustainable Development, and Impediments to Economic Advancement.